Low Serum 25‑hydroxyvitamin D levels: Predictive Value of Hematological and Inflammatory Markers in Patients with Urinary Tract Infection - Leila Pirdel; Manijeh Pirdel (Research in Molecular Medicine)
Background: Low vitamin D has been linked to enhance inflammatory markers in various pathological conditions. We aimed to evaluate the urinary tract infection (UTI)-associated hematological and inflammatory markers mediated by low serum levels of 25-hydroxyvitamin D [25(OH)D]. Methods: Vitamin D level, hematological indices (Neutrophil-to-lymphocyte ratio [NLR], Monocyte-to-lymphocyte ratio [MLR], Neutrophil-to-monocyte ratio [NMR], Platelet-to-lymphocyte ratio [PLR], and Mean platelet volume [MPV]), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6, and tumor necrosis factor-a were evaluated in 115 UTI patients and 57 controls. Results: The findings showed an inverse association between elevated hematological (NLR, MLR, and MPV) and serum markers of inflammation (CRP, IL-6, and TNF-a) with serum 25(OH)D levels in UTI patients. Among the several markers evaluated, the MLR had the ability to suggest the associated inflammation with low serum levels of 25(OH)D. Conclusion: The involvement of vitamin D deficiency might be characterized by an increase in the inflammatory markers in the patients which have an ability to establish the relationship between vitamin D deficiency and UTI; however, further investigations are needed to validate this finding.